The implementation of the Projek Penguatan Profil Pelajar Pancasila with the theme of Employment as an Effort to Achieve Vocational Education Goals - Kurniyawan, Handi; Rahmat, Rahmat; Tanshzil, Sri Wahyuni (Journal of Disruptive Learning Innovation (JODLI), 2023)
Unemployment is one of the social problems occurring in almost every country in the world. In Indonesia itself, unemployment is dominated by vocational school graduates. Ideally, vocational schools are educational institutions that emphasize the formation of students to be ready and capable of facing the demands of the workforce and industry. However, in reality, vocational school graduates contribute significantly to the high rate of open unemployment in Indonesia. Therefore, various efforts and strategies have been made by various parties including schools to address this issue. One of these strategies is through the Projek Penguatan Profil Pelajar Pancasila. Thus, the aim of this research is to describe and analyze the implementation of the Projek Penguatan Profil Pelajar Pancasila with the theme of employment as an effort to achieve vocational education goals carried out at SMK Syubbanul Wathon in Tegalrejo, Magelang Regency. The approach used in this research is qualitative research with a case study design. The techniques used by the researcher to collect research data are through interviews, observations, and document studies. The results of this research indicate that the implementation of the Projek Penguatan Profil Pelajar Pancasila  with the theme of employment not only shapes students to have abilities according to the demands of the business world and industry through activities such as creating job application letters and CVs as well as interview simulations but also shapes characters in accordance with the Pancasila student profile needed to compete in the global competence arena and support and provide a strong foundation for the competencies possessed by students to avoid misdirection.